Misuse of appetite- stimulant drugs in Babylon# - K. Saleh, Shafaq (Iraqi Journal of Pharmaceutical Sciences, 2017)
Drug misuse is defined as using of drugs for a non-therapeutic or non-medical purpose. In Iraq drug misuse is a major problem because almost any drug can be easily obtained from pharmacies. Appetite- stimulant drugs are example of drugs that are widely used without a prescription. The study included 230 patients who use these drugs in Babylon. A questionnaire included the following questions ; age, sex, marital state, the reason for use the drug , whether the drug is prescribed by physician or not , type of drug used , the frequency of daily dose and lastly the extent of side effects of the drugs used. The results showed that the age range of 35% of subjects were (17-21) years old and 70% of participants were females. The study also showed that 62% of them are unmarried and the reason for use, in 48% of subjects, was to increase the body weight. Furthermore, this study revealed that about 68% of those subjects utilized these drugs without prescription and the steroids are the most drug type used (33%). Additionally, 44% of subjects used these drugs twice daily and 80% of subjects who used steroids developed marked side effects. It can be concluded that there is a misuse of appetite- stimulant drugs in subjects participated in this study and most of these drugs are not used on therapeutic or scientific bases.Key words : Misuse of drug , appetite-stimulant, dexamethasone.